1982
DOI: 10.1002/pros.2990030205
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid binding protein in normal and neoplastic rat prostate

Abstract: Sucrose density gradient analysis of cytosol from normal and neoplastic rat prostatic tissues exhibited a peak of (3H) retinoic acid binding in the 2S region, corresponding to the cytoplasmic retinoic acid binding protein (cRABP). In the Fisher-Copenhagen F1 rat, cRABP was present in the lateral lobe, but could not be detected in the ventral nor in the dorsal prostatic lobes. Four sublines of the R-3327 rat prostatic tumor contained similar levels of this binding protein. The absence of cRABP in the normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In organ culture studies of prostate tissue, retinol was shown to reverse squamous metaplasia induced by treatment with chemical carcinogens (11,97). Retinol binding proteins have also been reported in prostate cells (18,50,83). We recently reported vitamin A concentrations in the prostate at 1-3 nmol/g, which is within a range where biological effects have been observed in vitro (25).…”
Section: Vitamin Amentioning
confidence: 65%
“…In organ culture studies of prostate tissue, retinol was shown to reverse squamous metaplasia induced by treatment with chemical carcinogens (11,97). Retinol binding proteins have also been reported in prostate cells (18,50,83). We recently reported vitamin A concentrations in the prostate at 1-3 nmol/g, which is within a range where biological effects have been observed in vitro (25).…”
Section: Vitamin Amentioning
confidence: 65%